The Influence of Power-Point Media on Student Learning Outcomes Fifth Grade students at SDIT Adzkia II Padang - Alfiyandri Alfiyandri; Lisa Yuniarti; Alfroki Martha (Jurnal Ilmiah Profesi Pendidikan, 2023)
The problem in this study is the low student learning outcomes in science learning. The difficulty can be seen from the lack of use of media in learning activities. Based on this, the researchers took the initiative to test a teaching aid media to improve student learning outcomes. The design of this study uses a Quasi Experimental Design with a design form Nonequivalent Control Group Design. The population in this study were fifth grade students at SDIT Adzkia II Padang, for the 2022/2023 academic year, with a total of 64 students. Sampling used probability sampling technique with Saturated Sampling method, which resulted in class V Thoif 1 as the experimental class, class V Thoif 2 as the control class. Based on the results of hypothesis testing with the t-test method, the data value tcount = 2.6772 with a difficulty level of 5% with the test criteria if tcount > ttable then H1 is accepted and H0 is rejected. Where the number of test takers in the experimental class was 32 students with an average of 74.0 while in the control class the number of test takers was 32 students with an average of 62.3. The standard deviation of the experimental class (S=15.6) is greater than the standard deviation of the experimental class 2 (S=20.5). The acquisition of the t-test value is tcount=2.6771and ttable = 1.999. The results showed There is an effect of the use of media power point on student learning outcomes in science material in the experimental class is better than student learning outcomes in science material in the control class SDIT Adzkia II Padang.